Pengaturan Mengenai Kecakapan Atas Jabatan Notaris yang Dinyatakan Pailit - Jovita Widiyanti, Fatma (CV. Rayyan Dwi Bharata, 2025)
This study examines the disharmony between Law No. 30 of 2004, as amended by Law No. 2 of 2014 on the Notary Profession (Undang-Undang Jabatan Notaris Nomor 1 Tahun 2014) and Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment (UUKPKPU) regarding the legal consequences for notaries declared bankrupt. Article 12(a) of Undang-Undang Jabatan Notaris Nomor 1 Tahun 2014 stipulates that a notary declared bankrupt by a final court decision must be dishonourably discharged, resulting in the loss of professional competence. Conversely, UUKPKPU only regulates the bankruptcy’s effect on the debtor’s assets, not professional status. This regulatory inconsistency contradicts the principles of justice and business continuity in bankruptcy law. The lack of synchronisation between these laws creates legal uncertainty for notaries. Therefore, normative and technical improvements to the Undang-Undang Jabatan Notaris Nomor 1 Tahun 2014 are needed, including adopting cyber notary concepts to accommodate electronic deed-making in line with technological advancements and legal practices in other jurisdictions, ensuring legal certainty for notaries in the digital era.